Imaging in gynecological disease (14): clinical and ultrasound characteristics of ovarian clear cell carcinoma. (5th December 2018) - Pozzati, F.; Moro, F.; Pasciuto, T.; Gallo, C.; Ciccarone, F.; Franchi, D.; Mancari, R.; Giunchi, S.; Timmerman, D.; Landolfo, C.; Epstein, E.; Chiappa, V.; et al.
ABSTRACT: Objective: To describe the clinical and ultrasound characteristics of ovarian pure clear cell carcinoma. Methods: This was a retrospective study involving data from 11 ultrasound centers. From the International Ovarian Tumor Analysis (IOTA) database, 105 patients who had undergone preoperative ultrasound examination by an experienced ultrasound examiner between 1999 and 2016 were identified with a histologically confirmed pure clear cell carcinoma of the ovary. An additional 47 patients diagnosed with pure clear cell carcinoma between 1999 and 2016 and with available complete preoperative ultrasound reports were identified retrospectively from the databases of the departments of gynecological oncology in the participating centers. The ultrasound images of all tumors were described using IOTA terminology. Clinical and ultrasound characteristics were analyzed for the whole group, and separately, for patients with and those without histologically confirmed endometriosis, and for patients with evidence of tumor developing from endometriosis. Results: Median age of the 152 patients was 53.5 (range, 28–92) years and 92/152 (60.5%) tumors were FIGO Stage I. Most tumors (128/152, 84.2%) were unilateral. On ultrasound examination, all tumors contained solid components and 36/152 (23.7%) were completely solid masses. The median largest diameter of the lesion was 117 (range, 25–310) mm. Papillary projections were present in 58/152 (38.2%) masses and, in most of these (51/56, 91.1%), vascularized papillary projections were seen. Information regarding the presence, site and type of pelvic endometriosis at histology was available for 130/152 patients. Endometriosis was noted in 54 (41.5%) of these. In 24/130 (18.6%) patients, the tumor was judged to have developed from endometriosis. Patients with, compared to those without, evidence of tumor developing from endometriosis were younger (median 47.5 vs 55.0 years, respectively), and ground‐glass echogenicity of cyst fluid was more common in pure clear cell cancers developing from endometriosis (10/20 vs 13/79 (50.0% vs 16.5%), respectively). Conclusions: Ovarian pure clear cell carcinoma is usually diagnosed at an early stage and typically appears as a large unilateral mass with solid components. Patients with clear cell carcinoma developing from endometriosis are younger than other patients with clear cell carcinoma, and clear cell cancers developing from endometriosis more often manifest ground‐glass echogenicity of cyst fluid. Copyright © 2018 ISUOG. Published by John Wiley & Sons Ltd.